Higher risk of revision in total knee arthroplasty after high tibial osteotomy: a systematic review and updated meta-analysis - Xi Chen; Zhen Yang; Hairui Li; Shibai Zhu; Yiou Wang; Wenwei Qian (BMC Musculoskeletal Disorders, 2020)
Abstract Background High tibial osteotomy is commonly performed in young patients with high activity demand. Several studies have reported outcome of HTO. The reported 10-year survival ranged from 79 to 97.6%. The reported 15-year survival ranged from 56 to 65.5%, resulting in the need for conversion to TKA. Primary TKA now provides satisfactory long-term outcome in terms of function and survival. Researches have been conducted to compare clinical outcome between primary TKA and TKA after HTO to see if TKA should be the prior treatment rather than HTO in some cases. But the results were inconsistent. This study aims to compare the risk of revision and other parameters between total knee arthroplasty after high tibial osteotomy and primary total knee arthroplasty. Methods Searches and screens of the relevant literature were conducted, after which data were extracted and pooled analysis was performed to compare the clinical outcomes between the two groups. Results A total of 14 studies with 144,692 cases were included. Pooled analysis showed significantly more revisions and complications, and more tibial component loosening and impingement in postoperative X-ray in the HTO-TKA group. Surgical complexity during conversion to total knee arthroplasty was summarised and listed in table. Conclusion High tibial osteotomy offers satisfactory pain relief and functional outcome in selected patients with high activity demand. However, the need for subsequent TKA should be noted, which might be a technically challenging procedure with significantly higher risk of revision comparing to primary TKA.